Proceedings of the ACM Symposium on Virtual Reality Software and Technology 2001
DOI: 10.1145/505008.505011
|View full text |Cite
|
Sign up to set email alerts
|

Inertial and magnetic posture tracking for inserting humans into networked virtual environments

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(58 citation statements)
references
References 5 publications
0
58
0
Order By: Relevance
“…Bachmann et al used accelerometers and magnetometers in a quaternion-based complementary filter to compensate the drift in orientation obtained from angular velocity [8,5]. The system combined a triaxial accelerometer, a triaxial gyroscope and a triaxial magnetometer assembled to produce a sensor module referred to as Magnetic, Angular Rate and Gravity sensor (MARG).…”
Section: Inertial Sensors Algorithmsmentioning
confidence: 99%
“…Bachmann et al used accelerometers and magnetometers in a quaternion-based complementary filter to compensate the drift in orientation obtained from angular velocity [8,5]. The system combined a triaxial accelerometer, a triaxial gyroscope and a triaxial magnetometer assembled to produce a sensor module referred to as Magnetic, Angular Rate and Gravity sensor (MARG).…”
Section: Inertial Sensors Algorithmsmentioning
confidence: 99%
“…Body tracking suits were proposed in [42] and [43], with multiple sensors positioned at various points across the body. The former work tested a single instance of their iNEMO sensors, comprised of an accelerometer, gyroscope and magnetometer, against commercial inertial sensors like those by Xsens [44].…”
Section: Related Workmentioning
confidence: 99%
“…Complementary filter design: Complementary filter exploit the complementary spectral characteristics of noisy signals to compute orientation [10]. While complementary filter can be operated at low computational costs, it has been shown that they are capable to track orientation of human body limbs with a sufficient accuracy [4].…”
Section: A Algorithms For Computation Of Orientationmentioning
confidence: 99%